2021
DOI: 10.3897/vz.71.e73146
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Myotis (Chiroptera, Vespertilionidae) from Uruguay

Abstract: The genus Myotis comprises a diverse group of vesper bats with worldwide distribution. Twenty-eight neotropical species are currently recognized. Based on a morphological approach, we describe a new species of Myotis from the Uruguayan Pampas grasslands, an ecoregion under high anthropogenic pressure with a largely unknown bat fauna. Qualitative and quantitative morphological analyses support the recognition of the new species and we present a set of external and cranial diagnostic characters by comparing them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…was only genus-level confirmed because Myotis taxonomy in the southern cone is still difficult, and genetic reference sequences are scarce. As an example, recently, a new Myotis species was described from individuals from Uruguay with no genetic material available [45].…”
Section: Discussionmentioning
confidence: 99%
“…was only genus-level confirmed because Myotis taxonomy in the southern cone is still difficult, and genetic reference sequences are scarce. As an example, recently, a new Myotis species was described from individuals from Uruguay with no genetic material available [45].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Argentine Yungas have received an extensive sampling effort for the bat assemblage during the past 50 years (Barquez and Díaz 2001;Gamboa-Alurralde et al 2017), the discovery of M. barquezi reveals the need for continued field sampling, associated with careful taxonomic investigations. In addition, there is the possibility of occurrence of other Myotis in Argentina not included in this study, for example M. pampa, a species recently described from pampa grassland in Uruguay close to the Argentina boundary (Novaes et al 2021c).…”
Section: Discussionmentioning
confidence: 99%
“…Myotis Kaup, 1829 currently comprises more than 140 species distributed worldwide, and 24 are recognized from South America (Moratelli et al 2019a(Moratelli et al , 2019bCarrión-Bonilla and Cook 2020;Novaes et al 2021aNovaes et al , 2021bNovaes et al , 2021cMDD 2022). Recent taxonomic reviews revealed a high diversity within Myotis (e.g., Moratelli et al 2011aMoratelli et al , 2013Moratelli et al , 2016Moratelli et al , 2017Moratelli et al , 2019bNovaes et al 2021aNovaes et al , 2021bNovaes et al , 2021c, refuting the hypothesis of LaVal that indicated a relatively low number of species in South America due to late colonization, and competition with other well-established insectivorous bat lineages (LaVal 1973). Although the arrival of Myotis in South America is estimated for the Plio-Pleistocene interval, the genus has undergone a fast and wide-ranging process of diversification (Stadelmann et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cranial and other external dimensions were taken using digital calipers accurate to 0.01 mm, including: forearm length (FA), third metacarpal length (3MC), length of dorsal hair (LDF), length of ventral hair (LVF), greatest length of skull (GLS), condylocanine length (CCL), condylobasal length (CBL), condylo-incisive length (CIL), basal length (BAL), zygomatic breadth (ZB), mastoid breadth (MAB), braincase breadth (BCB), interorbital breadth (IOB), postorbital breadth (POB), breadth across canines (BAC), breadth across molars (BAM), maxillary toothrow length (MTL), length of the upper molars (M1-3), mandibular length (MAL), and mandibular toothrow length (MAN). These measurements are described in detail by Novaes et al (2021b). Capitalized color nomenclature follows Ridgway (1912).…”
Section: Methodsmentioning
confidence: 99%
“…The South American Myotis is a taxonomic puzzle due to morphological similarity among species phylogenetically close. Consequently, there are cryptic species of Myotis and recent systematic reviews have demonstrated the existence of independent evolutionary lineages being treated as a unique species (Larsen et al 2012, Carrión-Bonilla and Cook 2020, Novaes et al 2021a, 2021b, 2021c. Myotis atacamensis is at the center of this debate, where populations from northern and central western Peru misidentified as M. atacamensis were recently described as a new species (Moratelli et al 2019b).…”
Section: Introductionmentioning
confidence: 99%